HEGEMONI MAKNA DAN STRATEGI PERSUASI DALAM IKLAN TOLAK ANGIN DAN ANTANGIN: SEBUAH ANALISIS WACANA KRITIS VAN DIJK - Endang Astuti; Asrofah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Advertising plays a strategic role in shaping public perceptions and reproducing ideology through consciously constructed linguistic forms. This study aims to reveal the hegemony of meaning and persuasive strategies in Tolak Angin and Antangin advertisements by employing Teun A. van Dijk’s Critical Discourse Analysis (CDA) approach. The research data consist of two video advertisements obtained from the YouTube platform, which were transcribed and analyzed based on three levels of discourse structure: macrostructure, superstructure, and microstructure. The results show that Tolak Angin advertisements construct a discourse of legitimacy through science, highlighting toxicity testing, efficacy testing, and quality control as foundations of consumer trust. In contrast, Antangin advertisements present narratives of everyday working-class life and build emotional closeness through informal language and representations of life struggles. These differing strategies reveal that advertising not only communicates product benefit claims but also manipulates symbols, values, and social experiences to instill certain images in the audience’s minds.